In the Eye of the Storm Jai Ram Reddy and the Politics of Postcolonial Fiji - V. Lal, Brij (ANU Press, 2010)
To read this evocative book is to be thrust into a Fiji that has, for the moment, been snuffed out by military might: a Fiji of political parties, parliamentary politics, elections, manifestoes, campaigns, democractic defence of interests, party manoeuvres, and constitutional protection of rights and freedoms. It is a comprehensive and eloquent re-telling of the story of Fiji politics from independence in 1970 to 1999 through the perspective of Fiji's greatest living statesman, Jai Ram Reddy, by one of the world's most distinguished scholars of its history and politics.